A Noble Metal Dichalcogenide for High‐Performance Field‐Effect Transistors and Broadband Photodetectors. (14th November 2019) - Wang, Zhen; Wang, Peng; Wang, Fang; Ye, Jiafu; He, Ting; Wu, Feng; Peng, Meng; Wu, Peisong; Chen, Yunfeng; Zhong, Fang; Xie, Runzhang; Cui, Zhuangzhuang; et al.
Abstract: 2D layered materials are an emerging class of low‐dimensional materials with unique physical and structural properties and extensive applications from novel nanoelectronics to multifunctional optoelectronics. However, the widely investigated 2D materials are strongly limited in high‐performance electronics and ultrabroadband photodetectors by their intrinsic weaknesses. Exploring the new and narrow bandgap 2D materials is very imminent and fundamental. A narrow‐bandgap noble metal dichalcogenide (PtS2 ) is demonstrated in this study. The few‐layer PtS2 field‐effect transistor exhibits excellent electronic mobility exceeding 62.5 cm 2 V −1 s −1 and ultrahigh on/off ratio over 10 6 at room temperature. The temperature‐dependent conductance and mobility of few‐layer PtS2 transistors show a direct metal‐to‐insulator transition and carrier scattering mechanisms, respectively. Remarkably, 2D PtS2 photodetectors with broadband photodetection from visible to mid‐infrared and a fast photoresponse time of 175 µs at 830 nm illumination for the first time are obtained at room temperature. Our work opens an avenue for 2D noble‐metal dichalcogenides to be applied in high‐performance electronic and mid‐infrared optoelectronic devices. Abstract : PtS2 has exhibited a huge promise for electronics and infrared photodetectors. Few‐layer PtS2 field‐effect transistors exhibit excellent electronic mobility exceeding 62.5 cm 2 V −1 s −1 and ultrahigh on–off ratio over 10 6 at room temperature. 2D PtS2 photodetectors with broadband photodetection from visible to mid‐infrared and a fast photoresponse time of 175 µs at 830 nm illumination are obtained at room temperature.